(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Serum potassium is a very sensitive serum electrolytes. Objective: The purpose of the present study was to see the immediate appearance of different clinical features among children depending on the serum potassium level. Methodology: This cross-sectional study was conducted in the Department of Pediatric Medicine at Institute of Child Health (ICH), Mirpur, Dhaka, Bangladesh from September 2011 to February 2012. Every consecutive child with both sexes admitted with acute watery diarrhea and vomiting of less than 14 days duration were enrolled in this study. The clinical manifestations that were observed in this study were neck flop, weakness of limbs, abdominal distention, diminished or absent bowel sounds. Serum potassium was measured from the venous blood. Result: A total number of 126 children were recruited for this study. Majority of the children (64.3%) were 2 to 12 months old followed by 13 to 24 months old children (27.0%). The abdominal distension was first developed at potassium level 3.4 mmol/L and highest number of patient developed this feature at potassium level 3.2 mmol/L. The neck flop was first developed at potassium level 3.4 mmol/L and highest number of patient developed this feature at potassium level 3.0 mmol/L. The diminished or absent bowel sound was first developed at potassium level 3.4 mmol/L. Conclusion: In conclusion abdominal distension, neck flop, diminished/absent bowel sound and muscular weakness are developed immediately after the changes of serum potassium level among the children presented with acute gastroenteritis. Journal of Current and Advance Medical Research, January 2021;8(1):44-48